Color stability of weathered heat-treated teak wood - Aparecida Garcia, Rosilei; de Oliveira Lopes, Juliana; do Nascimento, Alexandre Miguel; de Figueiredo Latorraca, João Vicente (Maderas. Ciencia y Tecnología, 2025)
This study investigated the color stability in a heat treatment of teak wood (Tectona grandis) exposed to ultraviolet radiation under accelerated aging conditions. Nine trees from three different spacing levels were used. Samples of 150 mm x 75 mm x 20 mm were prepared and divided into two groups: heartwood and sapwood. Two levels of heat treatment (180 and 200°C) were used. The color was measured every 42 hours with a portable spectrophotometer using the CIE-Lab system. Accelerated aging was performed in a QUV/Spray chamber. The total cycle of exposure to ultraviolet radiation was of 168 hours at 340 nm. Tree planting spacing had no effect on color change after ultraviolet radiation. Untreated sapwood had greater color change than untreated heartwood. However, after heat treatment, sapwood showed high color stability, especially at a temperature of 180°C.